Surgical rehearsal for mitral valve repair: personalizing surgical simulation by 3D printing - Fischer, Samantha; Romano, Gabriele; Sharan, Lalith; Warnecke, Gregor; Mereles, Derliz; Karck, Matthias; De Simone, Raffaele; Engelhardt, Sandy (The annals of thoracic surgery, 2023)
Purpose - The goal of this study was to show possible effects of performing the actual procedure of mitral valve repair (MVR) on personalized silicone models 1 day before operation. - Description - Based on preoperative 3-dimensional echocardiography recordings, flexible 3-dimensional replicas of the depicted pathologic mitral valves could be produced and used for a simulation of reconstructive techniques analogous to the upcoming MVR procedure. We integrated this step of personalized surgical planning into the clinical routine of 6 MVR cases with 3 different surgeons. This pilot study was assessed by evaluating questionnaires and by comparing isolated surgical steps with conventional MVRs. - Evaluation - This approach was considered a better preparation for MVRs with overall positive responses from the surgeons. Simulation helped reduce the time of initial inspection of the valve because of better understanding of the valve’s pathomorphologic features. Annuloplasty benefited from preoperative sizing by reducing the number of sizing attempts. - Conclusions - These initial findings suggest that simulation-based surgical planning can be implemented into patients’ and physicians’ clinical workflow as a major technologic advancement for future MVR preparation.
Online verfügbar 10. Januar 2023, Artikelversion 23. März 2023
Gesehen am 16.05.2023